2019
DOI: 10.1002/jcph.1453
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Drug Interaction Study to Assess the Effect of Cytochrome P450 Inhibition and Induction on the Pharmacokinetics of the Novel Cereblon Modulator Avadomide (CC‐122) in Healthy Adult Subjects

Abstract: Avadomide (CC‐122) is a novel immunomodulatory drug that binds to cereblon, a member of the Cullin 4‐RING E3 ubiquitin ligase complex. Avadomide has multiple pharmacologic activities including potent immune modulation, antiangiogenic, antitumor, and antiproliferative activity and is being evaluated as an oncology treatment for hematologic malignancies and advanced solid tumors. In vitro study has indicated that cytochrome P450 (CYP) 3A and CYP1A2 appear to be the major enzymes involved in the oxidative metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(69 reference statements)
2
7
0
Order By: Relevance
“…Therefore, PK in terms of total concentrations was analyzed in the current study. CC‐122 PK in healthy subjects from this study is generally similar to those in other studies of healthy subjects with normal function . This study also showed that consistent with renal excretion of unchanged parent CC‐122 being one of the major routes of elimination, renal impairment increases overall plasma exposure to CC‐122, as demonstrated by that in subjects with mild, moderate, and severe renal impairment, the total plasma exposure of CC‐122 increased by ∼20%, ∼50%, and ∼120%, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Therefore, PK in terms of total concentrations was analyzed in the current study. CC‐122 PK in healthy subjects from this study is generally similar to those in other studies of healthy subjects with normal function . This study also showed that consistent with renal excretion of unchanged parent CC‐122 being one of the major routes of elimination, renal impairment increases overall plasma exposure to CC‐122, as demonstrated by that in subjects with mild, moderate, and severe renal impairment, the total plasma exposure of CC‐122 increased by ∼20%, ∼50%, and ∼120%, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Plasma and urine samples were spiked with stable 13 C-labeled CC-122 as an internal standard (IS). CC-122 and [ 13 C 5 ]-CC-122 (IS) from K 3ethylenediaminetetraacetic acid (EDTA) human plasma were extracted by solid-phase extraction using a Tomtec Quadra 4 SPE system with Waters Oasis µ-Elution HLB plate (30 µm).…”
Section: Bioanalytical Methodologymentioning
confidence: 99%
See 3 more Smart Citations